The rehabilitation of triangular fibrocartilage complex (TFCC) repairs in tennis players - Pitts, G. (Medicine and Science in Tennis, 2006)
The professional and amateur tennis player faces many problems throughout their career. One of the most troublesome problems can be pain associated with the ulnar side of the wrist. If the tennis player is unfortunate to have a triangular fibrocartilage complex (TFCC) injury, then this can stop or alter their play for a long period of time. Fortunately, the skills of the current surgeons have allowed the tennis player to resume a competitive level of tennis with repair of this complicated structure. The article describes what is possible and necessary during rehabilitation after TFCC repairs in tennis players.